Website users’ segmentation to promote library resources and services - A. E. Rykhtorova; O. M. Udartseva (Библиосфера)
The article is devoted to the review of the effectiveness main indicators to promote library resources and services related to the intended target audience evidently for the State Public Scientific Technological Library of the Siberian Branch of the Russian Academy of Sciences (SPSTL SB RAS) website. To consider a number of indicators for creating a simplified EMO (electronic marketing orientation) model of an organization, the authors attempt to track the ratio of users belonging to the intended target audience, with the overall activity of Russian users.